Compression garment wear and sensory variables after burn: a single-site study. Issue 8 (December 2020) - Crofton, E.; Meredith, P.J.; Gray, P.; Strong, J.
Abstract: Objective: Compression garments are well accepted as routine practice for scar management after burn. In a recent systematic review, six main reasons for compression garment non-adherence were identified including sensory disturbances. To further understand the impact of sensory issues, the aim of the present study is to investigate associations between sensory variables and compression garment wear. Method: Adults ( N  = 117) attending a quaternary adult burns outpatient clinic completed: The Adolescent/Adult Sensory Profile; a custom-designed compression garment wear questionnaire; and three quantitative sensory testing procedures (Two-Point Discrimination, Mechanical Detection Threshold and Pressure Pain Threshold). Results: Patients who reported lower Pressure Pain Threshold or Mechanical Detection Threshold, higher acuity for Two Point Discrimination, and higher than average sensory avoiding and sensory sensitivity patterns were less adherent with garment wear. Conclusions: Overall, sensory factors assessed using both self-report and quantitative sensory testing were associated with compression garment adherence. This knowledge suggests the value in developing and evaluating sensory-informed treatment strategies to improve compression garment wear.